Synergistic Enhancement of Lung Cancer Therapy Through Nanocarrier‐Mediated Sequential Delivery of Superantigen and Tyrosin Kinase Inhibitor. (20th June 2014) - Li, Da; Li, Yongbin; Xing, Haibo; Guo, Junling; Ping, Yuan; Tang, Guping
<x xml:space="preserve">Abstract</x> Gefitinib (GFT) and other tyrosine kinase inhibitors (TKIs) have been widely used for the treatment of advanced or metastatic lung cancer due to their reduced side effects when compared to classic cytotoxic chemotherapeutic agents. However, both intrinsic and acquired resistance often hinders the effectiveness of TKIs. Based on recent findings that the outcome of chemotherapy can be influenced by the host immune system at multiple levels, an exploration of whether activating antitumor immunity improves the efficacy of the targeted cancer therapy of TKIs is undertaken. To this end, a cationic carrier is used to deliver superantigen and GFT in a simultaneous or sequential manner. The sequential delivery of superantigen and GFT can significantly enhance T cell immunity, promote cytokine production, inhibit tumor growth, and prolong survival time in tumor models with lung carcinoma xenografts. Most importantly, dual sequential treatment reveals a synergistic effect on tumor inhibition, which is much more effective than the monotherapy of either GFT or pTSA, as well as the combined treatment through simultaneous codelivery of pTSA and GFT together. This study demonstrates the important contribution of immunotherapy to targeted molecular therapy and opens up new possibilities for treating a wide spectrum of cancers.